Crystal containing Zn and Fe, preparation method of crystal and application of crystal in catalytic synthesis of dimethyl carbonate

By developing a crystal catalyst containing Zn and Fe, and using its three-dimensional porous structure to improve catalytic activity, the problem of low catalytic performance of existing catalysts in the direct synthesis of dimethyl carbonate by CO2 and methanol is solved, and efficient catalysis and High yield effect.

CN119462486AActive Publication Date: 2025-02-18FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411404351.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-02-18
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

The catalytic performance of existing catalysts is not high enough in the direct synthesis of dimethyl carbonate by CO2 and methanol, and it is necessary to develop new catalysts with clear structure and excellent performance.

Method used

A crystal catalyst containing Zn and Fe is provided, with the chemical formula Zn3(cpb)2[Fe(CN)6]2·nH2O, and a three-dimensional porous structure is formed by bridging between the ligand cpb and metal ions to improve catalytic activity.

Benefits of technology

The catalyst efficiently catalyzes the reaction of CO2 and methanol to form dimethyl carbonate under 5MPa and 180°C. The yield of dimethyl carbonate reaches 16.8 mmol/gcat, and the preparation method can control the obtaining of high-quality single crystals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462486A_ABST
    Figure CN119462486A_ABST
Patent Text Reader

Abstract

The invention discloses a crystal containing Zn and Fe and a preparation method and application thereof. The chemical formula of the crystal containing Zn and Fe is Zn3 (cpb) 2 [Fe (CN) 6] 2. NH2O, wherein the ligand cpb is 1-(3-carboxyl benzene)-4, 4 '-dipyridyl viologen onium salt. The crystal containing Zn and Fe provided by the invention has thermochromic performance, the crystalline catalyst after heating stimulation can effectively catalyze CO2 and methanol to directly synthesize dimethyl carbonate, and compared with a crystal without heating stimulation, the performance is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a crystal containing Zn and Fe and a preparation method and application thereof, belonging to the field of catalysts. Background Art

[0002] Dimethyl carbonate is a green chemical widely used in the production of polycarbonate and as a solvent for lithium batteries and high-end coatings. Its potential use is as a gasoline and diesel additive. Its production technologies mainly include phosgene method, ester exchange method, CO esterification method or methanol oxidation carbonylation method. The phosgene method has been eliminated because the raw material phosgene is highly toxic. The ester exchange method produces equivalent by-products (propylene glycol or ethylene glycol), which makes its production cost very high. CO esterification method or methanol oxidation carbonylation method is the current development direction. From the perspective of carbon emission reduction, the direct synthesis of dimethyl carbonate using CO2 and methanol has the most atom economy and application prospects.

[0003] For the direct synthesis of dimethyl carbonate from CO2 and methanol, people have developed various types of catalysts such as CeO2, ZrO2, heteropoly acids, and metal-organic framework (MOFs) compounds, but their catalytic performance is not high enough, and it is necessary to further develop new catalysts with clear structures and excellent performance. Summary of the invention

[0004] According to a first aspect of the present application, a crystal containing Zn and Fe is provided.

[0005] A crystal containing Zn and Fe, the crystal having the chemical formula shown below:

[0006] Zn3(cpb)2[Fe(CN)6]2·nH2O;

[0007] The ligand cpb is 1-(3-carboxyphenyl)-4,4'-bipyridyl viologenium salt.

[0008] Optionally, the structure of the crystal is:

[0009] Cyanide and viologen ligands bridge Zn and Fe metal ions to form a three-dimensional porous structure with one-dimensional pores filled with guest molecules.

[0010] Specifically, there are two free ends in the cpb ligand, one is provided by the N in the terminal pyridine ring, and the other is provided by the carboxylate group. The two free ends are connected to two Zn ions, respectively, to form a closed two-dimensional organic layer structure.

[0011] One of the Zn ions is a four-coordinated trigonal pyramid structure, and its coordinated atoms are a carboxyl oxygen atom in a viologen ligand and three cyanogen nitrogen atoms. The other Zn ion is a six-coordinated octahedral structure, and its coordinated atoms are nitrogen atoms in two different viologen ligands and four cyanogen nitrogen atoms.

[0012] The organic layers are extended into a three-dimensional framework through ferrocyanate bridges.

[0013] Optionally, the crystal belongs to the monoclinic system, P21 / c space group.

[0014] Optionally, the crystallographic data of the crystal is:

[0015] α=90°, β=92.2~93.5°, γ=90°;

[0016] Z=2.

[0017] Specifically, the crystallographic data of the crystal are:

[0018]

[0019] α=90(3)°, β=92.789(4)-93.159(4)°, γ=90(3)°; Z=2.

[0020] According to a second aspect of the present application, a method for preparing the above-mentioned crystal is provided.

[0021] A method for preparing the crystal described above comprises at least the following steps:

[0022] a) obtaining a ligand cpb;

[0023] b) placing a raw material containing a ligand cpb, a Zn source, K3[Fe(CN)6] and water in a sealed container and crystallizing to obtain the crystal.

[0024] Optionally, in step b), the Zn source is selected from at least one of zinc nitrate and zinc chloride.

[0025] Optionally, the molar ratio of the ligand cpb, Zn source, and K3[Fe(CN)6] is 1-4:1-2:1-2.

[0027] Optionally, the crystallization condition is: crystallization at room temperature for 5 to 10 days.

[0028] Specifically, the crystallization condition is: crystallization at room temperature for one week.

[0029] In step a), obtaining the ligand cpb is known, such as a modification based on a known method (reference Helvetica Chimica Acta, 2005, 88, 3200).

[0030] Specifically, in step (a), the preparation method of the ligand cpb can be any suitable method in the prior art, and this application does not strictly limit it. First, dinitrochlorobenzene and 4,4'-bipyridine are added to a 100mL round-bottom flask in a ratio of 1:1, and about 20-40mL of acetone are added, and refluxed at 60°C for one day. Filter, wash the obtained solid powder with ether three times to obtain an intermediate; then add the obtained intermediate and m-aminophenyl acid to a 100mL round-bottom flask in a ratio of 1:1.5, add about 20-40mL of ethanol, and reflux at 90°C for one day. Cool, add an appropriate amount of triethylamine and stir until a beige precipitate is produced, filter, and wash the obtained solid powder with ether three times to obtain the ligand cpb.

[0031] Optionally, in step b), the crystals are obtained by a diffusion method using a large beaker inside a small beaker.

[0032] Specifically, in step b), the ligand cpb, the Zn source and K3Fe(CN)6 are dissolved in a small amount of water respectively. Two beakers of different volumes are filled with water, wherein the small beaker is placed inside the large beaker. The aqueous solutions of the cpb ligand and the Zn source are injected into the small beaker with a syringe, and the aqueous solution of K3Fe(CN)6 is injected into the large beaker. The water level in the large beaker is about 1 cm higher than that in the small beaker, and then the beaker is covered with plastic wrap and left to stand for a week to grow crystals.

[0033] According to a third aspect of the present application, a crystalline catalyst is provided.

[0034] A crystalline catalyst, wherein the crystalline catalyst is obtained by heating and stimulating a crystal containing Zn and Fe;

[0035] The crystals containing Zn and Fe are selected from the crystals described above.

[0036] Optionally, the heating temperature is 140-180°C.

[0037] The crystals containing Zn and Fe are heated to obtain a thermochromic crystalline catalyst, which can be a block of crystals or a crystal powder.

[0038] According to a fourth aspect of the present application, an application of the above-mentioned crystalline catalyst is provided.

[0039] The application of the above-mentioned crystalline catalyst in the direct synthesis of dimethyl carbonate from CO2 and methanol, the reaction conditions are:

[0040] The reaction pressure is 3-7 MPa, the reaction temperature is 120-180° C., and the reaction time is 1-5 hours.

[0041] Under the conditions of reaction pressure of 3-7 MPa and reaction temperature of 120-180° C., CO2 and methanol are contacted with the crystalline catalyst and efficiently converted into dimethyl carbonate.

[0042] The beneficial effects of this application include:

[0043] 1) The crystalline catalyst provided in this application efficiently catalyzes the reaction of CO2 and methanol to produce dimethyl carbonate under the conditions of 5MPa and 180°C, and the yield of dimethyl carbonate reaches 16.8mmol / g cat. .

[0044] 2) The method for preparing crystals containing Zn and Fe provided in the present application has a controlled synthesis process and can obtain high-quality single crystals. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 Schematic diagram of the three-dimensional structure of crystalline PMOF-2A;

[0046] Figure 2 The structure diagram of crystalline PMOF-2A and crystalline catalyst PMOF-2B obtained after heating stimulation;

[0047] Figure 3 Powder X-ray diffraction patterns of PMOF-2A and PMOF-2B. DETAILED DESCRIPTION

[0048] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0049] Example 1 Synthesis of Ligand cpb

[0050] Synthesis process: First, add dinitrochlorobenzene and 4,4'-bipyridine in a 1:1 ratio to a 100mL round-bottom flask, add about 30mL of acetone, and reflux at 60°C for one day. Filter, wash the obtained solid powder with ether three times to obtain an intermediate; then add the obtained intermediate and m-aminophenyl acid in a 1:1.5 ratio to a 100mL round-bottom flask, add about 30mL of ethanol, and reflux at 90°C for one day. Cool, add an appropriate amount of triethylamine and stir until a beige precipitate is produced, filter, and wash the obtained solid powder with ether three times to obtain the ligand cpb.

[0051] Example 2 Preparation of crystalline catalyst

[0052] Dissolve zinc nitrate hexahydrate (297 mg), cpb ligand (456 mg) and potassium ferrocyanide (329 mg) in water respectively, then fill two beakers of different volumes with water, with the small beaker inside the large beaker. Use a syringe to inject the aqueous solution of cpb ligand and Zn source into the small beaker, and inject the aqueous solution of K3Fe(CN)6 into the large beaker. The water level in the large beaker is about 1 cm higher than that in the small beaker. Then cover the beaker with plastic wrap and let it stand for a week to form crystals, and obtain crystals with the chemical formula of Zn3(cpb)2[Fe(CN)6]2·nH2O, which is recorded as PMOF-2A.

[0053] PMOF-2A was heated at 160°C to obtain PMOF-2B.

[0054] Example 3 Structural Characterization of Samples

[0055] The X-ray powder diffraction phase analysis (XRD) of the ground crystalline PMOF-2A and PMOF-2B was carried out on a Rigaku MiniFlexⅡ X-ray diffractometer, with a Cu target and a Kα radiation source (λ=0.154184 nm). The results showed that the sample prepared in Example 2 was a sample of high purity and high crystallinity.

[0056] The X-ray single crystal diffraction of crystalline PMOF-2A and PMOF-2B was carried out on a Mercury CCD single crystal diffractometer, with Mo target, Kα radiation source (λ=0.07107nm), and test temperature 293K. The structure was analyzed by Shelxtl97. The XRD diffraction theoretical spectrum calculated by importing the single crystal diffraction structure data cif file into the software Mercury3.5 was compared with the experimentally measured XRD diffraction spectrum as shown in the figure. Figure 3 As shown, it can be seen that the XRD diffraction pattern obtained by fitting the single crystal data is highly consistent with the XRD diffraction pattern measured experimentally, proving that the obtained sample is a sample of high purity and high crystallinity.

[0057] X-ray powder diffraction and single crystal diffraction results show that:

[0058] Crystalline PMOF-2A and PMOF-2B both belong to the monoclinic P21 / c space group. The metal Zn ions are bridged by two ligands to form a three-dimensional framework structure with three-fold overlaps, which has one-dimensional holes filled with guest molecules. Figure 1The figure is a schematic diagram of the three-dimensional structure of crystalline PMOF-2A. There are two free ends in the cpb ligand, one is provided by the N in the terminal pyridine ring, and the other is provided by the carboxylate. The two free ends are connected to two Zn ions, respectively, to form a closed two-dimensional organic layer structure. One of the Zn ions is a four-coordinated triangular pyramid structure, and its coordinated atoms are a carboxyl oxygen atom and three cyanogen nitrogen atoms in a viologen ligand. The other Zn ion is a six-coordinated octahedral structure, and its coordinated atoms are nitrogen atoms and four cyanogen nitrogen atoms in two different viologen ligands. The organic layer is extended into a three-dimensional framework through ferrocyanate bridges.

[0059] Among them, the specific structures of PMOF-2A and PMOF-2B are as follows Figure 2 shown.

[0060] Specifically, the unit cell parameters of PMOF-2A are: α=90(3)°, β=93.159(4)°, γ=90(3)°; Z = 2. Specifically, the unit cell parameters of PMOF-2B are: α=90(3)°, β=92.789(4)°, γ=90(3)°; Z=2.

[0061] Example 4 Application of crystalline catalyst in the reaction of CO2 and methanol catalyzing the synthesis of dimethyl carbonate

[0062] The direct synthesis of dimethyl carbonate from CO2 and methanol is carried out in a high-pressure reactor, accompanied by stirring and heating. 20 mg of the above-mentioned crystalline catalyst PMOF-2A or PMOF-2B is placed in a reactor, 5 mL of methanol is added, and the high-pressure reactor is closed. Before the reaction, the reactor air inlet valve is opened, a certain amount of CO2 is filled into the reactor, the air inlet valve is closed, the air outlet valve is opened to discharge the gas in the reactor to replace the air in the reactor, and this step is repeated 3 times. Finally, CO2 is introduced until the pressure in the reactor reaches 3 to 7 MPa. Turn on the heating, raise the temperature to 120 to 180 ° C, and stir the reaction for 1 to 5 hours. After the reaction is completed, wait for the reactor to cool to room temperature, release the pressure, and take out the reaction liquid. Use a centrifuge to separate the catalyst and the reaction liquid. Take the upper layer of the reaction liquid, use a gas chromatograph for quantitative analysis, and calculate the yield of dimethyl carbonate. The performance results of the crystalline catalyst are shown in Table 1.

[0063] Table 1. Performance of crystalline catalyst for direct synthesis of dimethyl carbonate from CO2 and methanol

[0064] Reaction conditions PMOF-2A PMOF-2B Pressure, temperature, time <![CDATA[Yield (mmol / g cat. )]]> <![CDATA[Yield (mmol / g cat. )]]> 3MPa, 140℃, 3 hours 0.9 6.6 3MPa, 160℃, 3 hours 7.5 8.9 5MPa, 120℃, 1 hour 0.4 10.5 5MPa, 120℃, 3 hours 0.6 12.6 5MPa, 140℃, 3 hours 1.7 13.1 5MPa, 160℃, 3 hours 12.2 13.7 5MPa, 160℃, 5 hours 14.5 16.2 5MPa, 180℃, 3 hours 16.1 16.8 7MPa, 140℃, 3 hours 2.2 15.4 7MPa, 160℃, 3 hours 15.2 16.7

[0065] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A crystal containing Zn and Fe, characterized in that: The crystal has the chemical formula shown below: Zn3(cpb)2[Fe(CN)6]2·nH2O; The ligand cpb is 1-(3-carboxyphenyl)-4,4'-bipyridyl viologenium salt.

2. The crystal according to claim 1, characterized in that The structure of the crystal is: Cyanide and viologen ligands bridge Zn and Fe metal ions to form a three-dimensional porous structure with one-dimensional pores filled with guest molecules; Preferably, the cpb ligand has two free ends, one is provided by the N in the terminal pyridine ring, and the other is provided by the carboxylate group, and the two free ends are respectively connected to two Zn ions to form a closed two-dimensional organic layer structure; One of the Zn ions is a four-coordinated trigonal pyramid structure, and its coordinated atoms are a carboxyl oxygen atom in a viologen ligand and three cyanogen nitrogen atoms. The other Zn ion is a six-coordinated octahedral structure, and its coordinated atoms are nitrogen atoms in two different viologen ligands and four cyanogen nitrogen atoms. The organic layers are extended into a three-dimensional framework through ferrocyanate bridges.

3. The crystal according to claim 1, characterized in that The crystal belongs to the monoclinic system, P21 / c space group; Preferably, the crystallographic data of the crystal are: α=90°, β=92.2~93.5°, γ=90°; Z=2。 4. A method for preparing the crystal according to any one of claims 1 to 3, characterized in that: At least the following steps are included: a) obtaining a ligand cpb; b) placing a raw material containing a ligand cpb, a Zn source, K3[Fe(CN)6] and water in a sealed container and crystallizing to obtain the crystal.

5. The method according to claim 4, characterized in that In step b), the Zn source is selected from at least one of zinc nitrate and zinc chloride.

6. The method according to claim 4, characterized in that The molar dosage ratio of the ligand cpb, Zn source and K3[Fe(CN)6] is 1-4:1-2:1-2.

7. The method according to claim 4, characterized in that The crystallization conditions are: crystallization at room temperature for 5 to 10 days.

8. A crystalline catalyst, characterized in that: The crystalline catalyst is obtained by heating and stimulating crystals containing Zn and Fe; The Zn- and Fe-containing crystal is selected from the crystals according to any one of claims 1 to 3.

9. The crystalline catalyst according to claim 8, characterized in that The heating temperature is 140-180°C.

10. Use of the crystalline catalyst according to claim 8 or 9 in the direct synthesis of dimethyl carbonate from CO2 and methanol, characterized in that: The reaction conditions are: The reaction pressure is 3-7 MPa, the reaction temperature is 120-180° C., and the reaction time is 1-5 hours.

Citation Information

Patent Citations

  • Zinc complex single crystal with reversible photochromic performance and preparation method thereof

    CN107573281A

  • Color-changing organic-inorganic hybrid material, and preparation method and application of material

    CN108484646A

  • MOFs crystal material, and preparation and application thereof

    CN109608652A

  • Application of viologen coordination compound crystal as multifunctional color-changing material

    CN112480149A

  • Preparation process of dimethyl carbonate and catalyst thereof

    CN114031500A